Endothelial dysfunction in development of cerebrovascular disorders in patients with diabetes mellitus - Evgenia Pavlovna Kosobyan; Ivona Renata Yarek-Martynova; Mikhail Yur'evich Martynov; Alla Nikolaevna Yasamanova; Tatiana Ivanovna Kolesnikova (Сахарный диабет, 2012)
Endothelial dysfunction and aberrations of haemostasis play an important part in development of cerebrovascular disorders in patientswith diabetes mellitus. Such factors as hyper- and hypoglycemia, hyperinsulinism, insulin resistance and excessive weight affect progressionof microcirculation deficiency and cerebral ischemia. Transcranial Doppler ultrasound examination is useful as a noninvasivemethod of hemodynamic assessment.